Development and application of decontamination methods for the re-use of laboratory grade plastic pipette tips. - Sang Hyuk Lee; William Kastor; Xiao Fu; Vikas Soni; Michael Keidar; Marc Donohue; Steve Wood; Enusha Karunasena (PLoS ONE)
During the SARS-CoV-2 pandemic, a need for methods to decontaminate and reuse personal protective equipment (PPE) and medical plastics became a priority. In this investigation we aimed to develop a contamination evaluation protocol for laboratory pipette tips, after decontamination. Decontamination methods tested in this study included cleaning with a common laboratory detergent (2.5% Alconox® solution followed with steam decontamination), exposure of ozone vapor at 250 and 14400 PPM * minute, and exposure to cold atmospheric plasma (CAP). All tips (control and experimental groups) were introduced to the methods described, while tips exposed to DNA extracts of Aeromonas hydrophila (ATCC-23211) were assessed for experimental groups. Decontamination was determined by turnover ratio and log reduction in detectable genomic material on the contaminated products using real-time quantitative PCR (qPCR) assay. Our results showed, cleaning tips with lab detergents along with steam decontamination removed genetic material, resulting in the highest log reduction, compared with ozone or CAP treatments. Detergent/washing methods showed the second highest turnover ratio (95.9%) and log reduction (5.943). However, the excessive residue (post- cleaning) on the plastic, within inner filters, and tip boxes suggested that washing with lab detergents was not favorable for reuse. Ozone vapor at 14400 PPM * minute showed the highest turnover ratio (98.4%) and log reduction (4.511). CAP exposure with tips inverted (the tip end exposed closer to the plasma flame) for 1 minute showed a turnover ratio of (68.3%) and log reduction (4.002). Relatively, lower turnover ratio and log reduction of CAP could be improved by optimization, such as increasing the exposure time. Future testing would provide fine-tuned conditions for CAP-specific decontamination of plasticware. In this study we were able to provide fundamental insight into a non-traditional decontamination method for single-use plasticware that could render these products reusable.